The centipede Lithobius celer (Chilopoda: Lithobiidae) in Wisconsin - (:unkn) unknown (My University, 1996)
The centipede Lithobius celer Bollman 1888 has been reported from Wisconsin only one time. Chamberlin (1911) provisionally referred specimens collected from unspecified Wisconsin and Michigan localities to this species, with considerable doubt since neither was a ''fully-grown male/' Subsequent investigators (e.g., Matthews 1935, Crabill 1958) did not report L. celer from the state. While examining specimens collected as part of an on-going prairie ecology study, I discovered a L. celer specimen from southern Wisconsin. The specimen was collected in a pitfall trap at Hawkhill Prairie, Dane County (T9N, R8E, Sec. 5) on 21 August 1986 by A. Lisken.
Keywords: centipede; Lithobius celer; Chilopoda; Lithobiidae; Wisconsin